Future accountants' attitudes towards business ethics / Kausar Yaakup - Yaakup, Kausar (2011)
Business ethics is a form of professional ethics that dwells on ethical principles and moral or ethical issues that arise in a business environment. Business ethics has been in the limelight of late due to numerous unethical business conducts which finally led to business collapse and shareholder loss. This study examines the attitude of potential future accountants to predict their attitude towards business ethics. This study investigates the relationship of religiosity and attitude towards business ethics. Apart from that, this study also highlighted the differences in attitude among genders and also the range in attitude towards business ethics among the three main ethnics in Malaysia. This study indicated religiosity has a positive significant relationship with ethical attitude. In terms of gender, this study showed that there is significant difference between males and females. Surprisingly, this study indicates that males are more ethical than females. With regard to ethnics, the result showed that there is no significant difference among Malays, Chinese and Indians in their attitude towards business ethics. Overall, this study indicated that future business leaders display high levels of ethical attitude and also high levels of religiosity. This can help the university management and future employer in promoting these students in the students' career path.